Adsorption of Linear Alkylbenzene Sulfonate (LAS) using Moringa oleifera Seeds - Manurung, Tety Wahyuningih; Ningsih, Rima Oktavia; Irawati, Utami (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
One of the main components in detergent is Linear Alkylbenzene Sulfonate (LAS), an anionic surfactant. In the aquatic environment, LAS has the potential to cause pollution and cannot be decomposed under anaerobic conditions (no air), so it is necessary to study processing methods that can reduce the concentration of LAS in the waters. In this research, a study of LAS adsorption by Moringa seeds was carried out. The parameters studied were the influence of contact time and solution pH. A study on the isothermic adsorption of LAS on Moringa seeds using the Freundlich and Langmuir approach was also carried out. The concentration of LAS was determined by the Methylene Blue Active Surfactant (MBAS) method using a UV-Vis spectrophotometer. The results showed that adsorption reached equilibrium after 90 minutes. A pH value of 5 is the optimum pH value for the adsorption of LAS by Moringa seeds. Using the Langmuir approach, the LAS adsorption capacity of Moringa seeds was calculated to be 400 mg/g.